Evaluating the predicted impact of changes to the AJCC/TMN staging system for differentiated thyroid cancer (DTC): A prospective observational study of patients in South East Scotland. (4th March 2019) - Hulse, Kate; Williamson, Adam; Gibb, Fraser W.; Conn, Brendan; Nixon, Iain J.
Abstract: Objectives: To assess the impact of the eighth edition AJCC/TMN staging system on patients with new diagnoses of differentiated thyroid cancers presenting to our regional multidisciplinary team meetings. Design: We analysed Endocrine Cancer MDT meeting records from 2009 to 2015 to identify all patients in the region presenting with a new diagnosis of differentiated thyroid cancer. We re‐staged patients according to the eighth edition AJCC/TNM staging classification and analysed the survival outcomes of patients in each stage under the seventh and eighth systems. Setting: Tertiary referral centre in South East Scotland (NHS Lothian). Participants: Three hundred and sixty‐one patients were newly diagnosed with DTC within South East Scotland during the study period and met our inclusion criteria. Main outcome measures: Disease‐specific mortality at any time during follow‐up. Results: In total, 119 of 361 (33%) patients were re‐staged when the eighth edition AJCC/TMN system was applied. The number of patients classified as having advanced stage (III/IV) disease fell from 76 (21%) to 8 (2%). The most common reason for down‐staging was re‐classification of tumour size, a factor in 96 (80.7%) down‐staged patients. The five‐year disease‐specific survival of the cohort overall was 98%. Overall, 7 (1.9%) thyroid cancer–related deaths occurred during follow‐up, three of whom were down‐staged. Conclusions: On implementation of the eighth edition of the AJCC/TMN staging system, we expect many patients who would previously have been considered to have advanced thyroid cancer will now be classified as early stage. This will accurately reflect their excellent survival outcomes.